Formulation and Effectiveness of Herbal Hair Dye from Ethanol Extract of Banyan Bark (Ficus benjamina L) - Safitri, Dewi; Tanjung, Siti Aisyah; Fitriani, Enny; Fatimah, Cut (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
The banyan plant (Ficus benjamina Linn.) is one of the plants that has benefit as a traditional medicine. Almost all parts of the plant have efficacy as a source of medicine and furniture or decoration. However, banyan bark is often considered waste. Based on the results of phytochemical screening that has been carried out, banyan bark contains chemical compounds tannins, saponins, flavonoids, alkaloids and glycosides. Flavonoids are a group of flavanols derived from benzene compounds that can be used as basic compounds of natural dyes. Therefore, the aim of this research is to try to make herbal hair dye using banyan bark (Ficus benjamina Linn.) as a natural dyeing ingredient. The research method used is experimental with 80% ethanol solvent. The formulation of herbal hair dye consists of extract of banyan bark (Ficus benjamina Linn), Piragalol, Xanthan gum, Methyl parabens, and BHT with concentration of 4%, 6% and 8%, respectively. Tests on the preparations made include organoleptic tests, homogeneity tests, viscosity tests, pH tests, stability tests, irritation tests, color stability tests produced, color stability tests against washing, color stability tests against sunlight and preference tests. The formulation of herbal hair dyes uses ethanol extract of banyan bark which can give color to gray hair with concentrations of ethanol extract of banyan bark 4%, 6% and 8%, Pyroganol 1%, Xanthan gum 1%, Methyl paraben and BHT. Banyan bark ethanol extract (Ficus benjamina Linn.) can be used in herbal hair dye by producing a blonde to dark brown color in gray hair. The best dye is obtained from the formula with concentration of 8% which consists of ethanol extract of banyan bark (EKBB) which produces a dark brown color, the pH of the preparation in the range of 5.8 – 6.1, the viscosity in the range of 2800 – 4800 cps, and the preparation is stable in several washes and exposure to direct sunlight and does not cause irritation reactions to the skin.